Everything's an argument with readings - Lunsford, Andrea A. (Bedford/st. Martin's, 2016)
Interactive exercises and tutorials for reading, writing, and research. LearningCurve adaptive, game-like practice that helps students focus on the topics where they need the most help, such as fallacies, claims, evidence, and other key elements of argument. Reading comprehension quizzes.